Association of urinary cadmium, circulating fatty acids, and risk of gestational diabetes mellitus: A nested case-control study in China. (April 2020) - Li, Xinping; Huang, Yichao; Xing, Yuling; Hu, Chen; Zhang, Wenxin; Tang, Yi; Su, Weijie; Huo, Xia; Zhou, Aifen; Xia, Wei; Xu, Shunqing; Chen, Da; et al.
Highlights: First study of mediation analysis on the relationship between Cd and risk of GDM via FAs. Higher Cd levels were associated with increased risk of GDM. Levels of Cd were associated with many kinds of FAs in different directions. Different subclasses of saturated FAs had distinct patterns of association with risk of GDM. Abstract: Background: Previous studies have observed that cadmium (Cd) exposure of pregnant women was associated with increased risk of gestational diabetes mellitus (GDM). However, the potential mechanism still remains unclear. In addition, various animal studies have suggested that Cd exposure could affect fatty acids (FAs) metabolism, but data on humans are scant. Objectives: We conducted a nested case-control study to investigate the associations of urinary Cd concentrations with levels of circulating FAs and risk of GDM in pregnant women, and further to examine the role of FAs in mediating the relationship between Cd exposure and risk of GDM. Methods: A total of 305 GDM cases were matched to 305 controls on pregnant women's age (±2 years) and infant's gender from a birth cohort study conducted in Wuhan, China. Urinary Cd concentrations and levels of plasma FAs between 10 and 16 gestational weeks were measured using inductively coupled plasma mass spectrometry and gas chromatography-mass spectrometry, respectively. Conditional logistic regressions models were used to estimate the associations of Cd concentrations and levels of FAs with the risk of GDM. Multiple linear regression models were applied to estimate the associations between Cd concentrations and levels of FAs. Mediation analysis was used to assess the mediating role of FAs in the association of Cd with the risk of GDM. Results: Urinary concentrations of Cd in cases (median: 0.69 μg/L) were significantly higher than controls (median: 0.59 μg/L, P < 0.05). Cd concentrations were positively associated with the risk of GDM ( P trend = 0.003). Compared to the first tertile of Cd, the adjusted odds ratios (95% confidence intervals) of GDM risk were 2.08 (1.29, 3.36) for the second tertile and 2.09 (1.32, 3.33) for the third tertile. Cd concentrations were positively correlated with levels of eicosadienoic acid and arachidonic acid/eicosapentaenoic acid ratio, but negatively correlated with levels of stearic acid, eicosapentaenoic acid, total odd-chain saturated fatty acids, total n-3 polyunsaturated fatty acids (PUFAs), and n-3 PUFAs/n-6 PUFAs ratio. We did not observe evidence that the association of Cd exposure and risk of GDM was mediated through FAs. Conclusions: Our findings confirmed the association of higher Cd exposure with increased risk of GDM in pregnant women, and provided forceful epidemiological evidence for the relation of Cd concentrations and levels of FAs.